The Phantom Unmasked : America's First Superhero - Patrick, Kevin, 1968- (Book collections on Project MUSE., 2017)
By tracing the publication history of The Phantom in magazines and comic books across international markets since the mid-1930s, author Kevin Patrick delves into the largely unexplored prehistory of modern media licensing industries.